Pengaruh Kandungan Partikel Cangkang Telur Terhadap Kekerasan dan Kekuatan Lentur Komposit Epoksi Setelah Paparan Panas - Anugrah Surya Arya Pranata; Shofiatul Ula; Iman Saefuloh; Agung Sudrajad; Ahmad Ali Alhamidi; Sunardi Sunardi (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Heat exposure can influence the changes in hardness and flexural strength of composites made from eggshell particles and bamboo fibers. The composite samples were prepared through cold compaction at 5 MPa for 2 hours. The materials were combined based on the following volume fractions: 50% epoxy resin, 10% alumina, 10% graphite, 5% zinc oxide (ZnO), and a 25% mixture of eggshell particles and bamboo fibers. The composite samples were then heated to 200°C for 1 hour. The final step involved curing, which required heating the samples in an electric oven at 150°C for 1 hour. Using a weighting method, the composite containing 25% eggshell particles achieved the optimal result, with a multi response performance index (MRPI) of 42.43. This composite exhibited hardness, modulus of elasticity (MOE), modulus of rupture (MOR), and strain values of 70.24 Shore D, 37.65 MPa, 8.58 MPa, and 0.78%, respectively. Conversely, the sample with 25% bamboo fiber and no eggshell particles demonstrated the highest flexural strength at 12.06 MPa, while the sample containing 25% eggshell particles recorded the highest hardness of 70.24 Shore D.